Nicaragua - Public Expenditure Review : Improving the Poverty Focus of Public Spending - World Bank (Washington, DC, 2013)
This Public Expenditure Review has two broad objectives. The first is to analyze the pattern and evolution of public expenditures in Nicaragua with a view toward assessing their consistency with the priorities expressed in the recent Poverty Reduction Strategy Paper (PRSP), as well as recommending ways to improve their poverty reducing impact. The PRSP puts heavy emphasis on the social sectors and the rural sectors: projects in these sectors account for 80 percent of the total portfolio of poverty reducing projects. Accordingly, the sector reviews in this report mainly focus on these two sectors plus transport, which has the single largest sector investment program. Municipal finances are not covered for lack of adequate information. The second objective of the PER is to diagnose Nicaragua's institutional capacity to implement the poverty reduction programs to be defined in the PRSP and recommend measures for raising that capacity. The Joint Staff Assessment of the Interim and full PRSP point toward the need to proioritize further the poverty reducing projects and programs envisaged by the government. Such a prioritization is likely to require a significant reallocation of public resources that could strain the limited capacity of the public sector's planning and budgeting framework. As part of this institutional diagnosis, the PER also evaluates the tracking mechanism to monitor the use of HIPC funds, and recommends measures for strengthening it.